Implementasi Analytic Hierarchy Process Sebagai Metode Penilaian Dalam Seleksi Calon Pemain Handball - Amar, Muh. Ikhsan; Cakrawijaya, Muhammad Hidayat (Building of Informatics, Technology and Science (BITS), 2021)
Any sports club would expect a good composition of players and in accordance with the standards that have been set. As in the Handball Sports Club. To obtain these players, it is necessary to carry out a selective and comprehensive recruitment. The process of recruiting players is a vital thing because it can determine the success and success of a sports club. This procession is not an easy matter, because it involves many player criteria that must be assessed and accumulating the results of the assessment also needs to be done with an objective method/algorithm. This study aims to design a scoring system for prospective handball players using the Analytic Hierarchy Process method and implemented into web-based software. The research process and system implementation use the Waterfal method which was developed according to the needs of the research. The results of this study are web-based software and criteria data and assessment sub-criteria consisting of posture criteria with height sub-criteria with eigenweights of 0.07 and body weight of 0.04, posture criteria with situp sub-criteria with eigenweights of 0.06, pushups 0.10, sprints 0.13, and shuttle run 0.14, and technical criteria with passing sub-criteria with eigenweight 0.16, flying shoot 0.14, and standing throw shoot with eigenweight 0.15. For the rating scale using a linguistic scale, the category is very good with an eigenweight of 0.55, good 0.26, quite good 0.12, and not good with an eigenweight of 0.05.